Cytological study in the Iraqi speeies of the genus Bromus L. Poaceae) - Baghdad Science Journal (مجلة بغداد للعلوم)
This paper is a part of a cytological studies of the genus Bromus L. in Iraq . Cl number for 103 specimens ropro^eming l^species determined . The course of meiosis including an analysis of chromosome configuradon for 27 collections belonging to 8 species were investigated . Meiosis was regular in most species . Tetraploid for B.scoparius L. (new cytotype ) and hexaploid ?'or " Kunth. were re^rted for the first time, cytological findings were supported the view of maintaining the closely related species B.danthoniae Trin. and B.lanceolatus Roth, as distinct species .